Analisis Implementasi Program Kelas Orang Tua Mengajar Di TKIT Baitusshalihin - Liliani, Dina; Munawwarah (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
Parental involvement in early childhood education is a crucial factor in supporting optimal child development. However, this involvement remains limited and has not been directly integrated into learning activities. Parents generally play only an administrative role, even though they have the potential to be a source of learning through their experience and profession. This study aims to describe the implementation of the Parent Teaching Class Program at Baitusshalihin Kindergarten (TKIT) Banda Aceh. This study used a descriptive qualitative approach, with five parents as teachers and one teacher as a companion. Data collection techniques were carried out through observation, interviews, and documentation. While data analysis used an interactive analysis model that includes data reduction, data presentation, and verification. The results showed that the program was implemented through planning, implementation, and evaluation stages. Parents taught according to their professional backgrounds using demonstration methods, direct practice, and question and answer sessions, along with concrete media. This program had a positive impact on children's courage, communication skills, and participation, and helped children learn about various professions contextually. In addition, this program strengthened the partnership between schools and families in supporting early childhood learning.